Jacobsthal Trigonometric Functions - Pakapongpun, Apisit; Chailangka, Natdanai (Journal of the Indonesian Mathematical Society, 2025)
Jacobsthal numbers satisfy a second order homogeneous recurrence relation $J_{n}=J_{n-1}+2J_{n-2}$ where $J_{n}$ denotes the $n^{th}$ Jacobsthal number. In this paper, the Jacobsthal sine, cosine, tangent and cotangent are defined, and some identities of Jacobsthal trigonometric functions are provided.